Characterization of Si3N4 powders in aqueous dispersions - S. Mello Castanho; R. Moreno (Cerâmica, 1998)
alpha- Si3N4 can easily oxidize when exposed in air atmosphere or other oxidizing environment. The chemistry of Si3N4 particle surfaces can change by different synthesis routes and also by subsequent processing steps. To avoid this oxidation is a challenge when Si3N4 powder is shaped by slip casting process from aqueous suspension. This study shows the variations on Si3N4 powder surface after slip casting process using x-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HTEM) on the green compacts. The results show that the dispersant used during the preparation of the slurry can reduce the level of oxidation of the Si3N4 particles when processing in aqueous solutions.